Dynamical behavior of He I-He II interface layer caused by forced heat flow - Murakami, M.; Kamiya, K.; Sato, T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The appearance and dynamical behavior of a He I-He II phase interface is experimentally investigated. The experimental mode in which nearly saturated He I initially at a little bit higher temperature than the lambda temperature is cooled by sudden evaporative cooling is primarily employed in the present experiment among several possibilities. In this mode where an interface appears and propagates downward, some dynamical aspects of an interface layer can be preferably investigated. The phenomenon is investigated by the application of Schlieren visualization method, and by measuring the temperature variation by superconductive temperature sensors and the pressure variation as well as the evaporating vapor flow rate which can be converted into the cooling rate.